Comparative Analysis of Bank Soundness Levels Using the RGEC Method at PT. Bank Muamalat and PT. Indonesian Sharia Bank - Nurfadillah Nurfadillah; Andi Bahri S; Damirah Damirah; Syahriyah Semaun; Muliati Muliati (Universitas Muhammadiyah Makassar, 2025)
Comparison between the health levels of Bank Muamalat , a national private bank, and Bank Syariah Indonesia, a state-owned enterprise, is based on their published 2022 annual financial statements. This study aims to assess the financial health of both banks and compare their health levels using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). The research employs a quantitative approach with a comparative field research type, focusing on financial health by analyzing financial performance in 2022 through the RGEC method. This study uses secondary data sourced from the 2022 annual reports of both banks, published by the Financial Services Authority (OJK). The findings indicate that Bank Muamalat performed well in liquidity and capital but needs improvement in profitability, particularly in return on assets. The composite rating for Bank Muamalat in 2022 was 68.57%, placing it in the PK-3 category, meaning it is 'Quite Healthy.' Bank Syariah Indonesia exhibited excellent performance in risk profile, capital, and operating margins. Its composite rating in 2022 was 74.28%, classifying it under the PK-2 category, meaning it is 'Healthy.' The different composite rankings suggest variations in financial health between the two banks. Future research is recommended to incorporate additional assessment factors and continue using the RGEC method to provide a more comprehensive evaluation of bank health.